Application of design of experiments to pharmaceutical formulation development. (1st January 2011) - Hwang, Richard; Noack, Robert M.
The pharmaceutical industry has come under immense pressure from shareholders and consumers to continuously improve product quality, reduce manufacturing costs and increase speed to develop new medicines. One area that impacts all of these quality, cost, and speed attributes is formulation development. The formulation of a pharmaceutical product includes the active pharmaceutical ingredient (API) and inactive ingredients that enable manufacturability and help the medicine achieve its effectiveness. Formulation scientists need to develop robust formulations while meeting aggressive timelines with limited amount of API. In order to achieve these challenging goals, formulation scientists must utilise proper experimental designs to develop formulations effectively. This article will provide a background on the formulation development process and explore one approach to use design of experiments (DOE) in the development of a tablet formulation. When the formulation and manufacturing process of a pharmaceutical product are optimised by a systematic approach using DOE, the product quality and cost can be effectively optimised.